Essential, unexceptional and universal: Teacher implicit beliefs of creativity. (December 2019) - Cropley, David H.; Patston, Timothy; Marrone, Rebecca L.; Kaufman, James C.
Highlights: Viewed through a new lens, teacher implicit beliefs of creativity reflect five factors. These factors are more differentiated and operationalized that the 4 Ps framework. The factors refute the existence of an arts-bias in teacher implicit beliefs. Differences exist, however, across gender, discipline, level and self-assessed creativity. These findings inform, and have implications for, teaching training and development. Abstract: Guided by four key elements of creativity theory (the 4 Ps), framed in an educational context (Results, Investigation, Students and Environment), this study examines implicit beliefs in a large sample of teachers across a range of discipline areas. The study finds that teacher implicit beliefs of creativity reflect a more differentiated and operationalized framework of five factors. Furthermore, these implicit beliefs are not indicative of a narrow, arts-biased understanding of creativity. Notwithstanding these results, the study also found differences among teachers by gender, discipline, level (elementary versus secondary), and even by the teachers' assessment of their own creativity. The implications of these results for teacher training and development are discussed.